Atypical presentation of diffuse lamellar keratitis after small‐incision lenticule extraction: Sterile multifocal inflammatory keratitis. Issue 6 (June 2018) - Stuart, Alastair; Reinstein, Dan Z.; Vida, Ryan S.; Archer, Timothy J.; Carp, Glenn
Abstract : N/A: We describe a case of atypical diffuse lamellar keratitis (DLK) following small‐incision lenticule extraction (SMILE). The patient presented with multiple focal white infiltrates 1 day after routine small‐incision lenticule extraction surgery. An interface washout was performed, and the patient was managed with intensive topical steroids. Potential infectious keratitis was also investigated (by culture and Gram stain) and treated aggressively with steroids and antibiotics. The cultures were all negative with no growth, and the focal infiltrates gradually resolved, with no relapses at the 15‐month postoperative follow‐up and a faint 0.7 mm superior scar in the right eye. This case highlights the importance of using intensive topical steroids as well as performing an interface washout in such cases because of the higher risk for corneal melting associated with focal infiltrates.